Thermodynamic approach to boron nitride nanotube solubility and dispersion. Issue 7 (3rd February 2016) - Tiano, A. L.; Gibbons, L.; Tsui, M.; Applin, S. I.; Silva, R.; Park, C.; Fay, C. C.
Abstract : Inadequate dispersion of nanomaterials is a critical issue that significantly limits the potential properties of nanocomposites and when overcome, will enable further enhancement of material properties. Abstract : Inadequate dispersion of nanomaterials is a critical issue that significantly limits the potential properties of nanocomposites and when overcome, will enable further enhancement of material properties. The most common methods used to improve dispersion include surface functionalization, surfactants, polymer wrapping, and sonication. Although these approaches have proven effective, they often achieve dispersion by altering the surface or structure of the nanomaterial and ultimately, their intrinsic properties. Co-solvents are commonly utilized in the polymer, paint, and art conservation industries to selectively dissolve materials. These co-solvents are utilized based on thermodynamic interaction parameters and are chosen so that the original materials are not affected. The same concept was applied to enhance the dispersion of boron nitride nanotubes (BNNTs) to facilitate the fabrication of BNNT nanocomposites. Of the solvents tested, dimethylacetamide (DMAc) exhibited the most stable, uniform dispersion of BNNTs, followed by N, N -dimethylformamide (DMF), acetone, and N -methyl-2-pyrrolidone (NMP). Utilizing the known Hansen solubility parameters of these solvents in comparison to the BNNT dispersion state, a region of good solubility was proposed. This solubility region was used to identify co-solvent systems that led to improved BNNT dispersion in poor solvents such as toluene, hexane, and ethanol. Incorporating the data from the co-solvent studies further refined the proposed solubility region. From this region, the Hansen solubility parameters for BNNTs are thought to lie at the midpoint of the solubility sphere: 16.8, 10.7, and 9.0 MPa 1/2 for δ d, δ p, and δ h, respectively, with a calculated Hildebrand parameter of 21.8 MPa 1/2 .